2022
DOI: 10.1038/s41598-022-17899-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of anti-proliferative and anti-oxidant effects of nano-sized vesicles from Brassica oleracea L. (Broccoli)

Abstract: In this in vitro study, we test our hypothesis that Broccoli-derived vesicles (BDVs), combining the anti-oxidant properties of their components and the advantages of their structure, can influence the metabolic activity of different cancer cell lines. BDVs were isolated from homogenized fresh broccoli (Brassica oleracea L.) using a sucrose gradient ultracentrifugation method and were characterized in terms of physical properties, such as particle size, morphology, and surface charge by transmission electron mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Broccoli has been widely studied for its anti-inflammatory and antioxidant properties against in vitro IBD models ( Table 1 [ [110] , [111] , [112] , [113] , [116] , [117] , [118] , [119] , [120] , [121] , [122] , [123] , [124] , [125] ] and Figure 1 ). One study showed that broccoli-derived nanoparticles (BDN), made of broccoli juice and lipids, prevented dendritic cell (DC) activation by upregulating AMPK anti-inflammatory pathways, thereby reducing chemoattractant molecules like chemokine (C-C) receptors (CCR), chemokine (CXC) ligand (CXCL), and CCLs in the DCs and monocytes [ 116 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Broccoli has been widely studied for its anti-inflammatory and antioxidant properties against in vitro IBD models ( Table 1 [ [110] , [111] , [112] , [113] , [116] , [117] , [118] , [119] , [120] , [121] , [122] , [123] , [124] , [125] ] and Figure 1 ). One study showed that broccoli-derived nanoparticles (BDN), made of broccoli juice and lipids, prevented dendritic cell (DC) activation by upregulating AMPK anti-inflammatory pathways, thereby reducing chemoattractant molecules like chemokine (C-C) receptors (CCR), chemokine (CXC) ligand (CXCL), and CCLs in the DCs and monocytes [ 116 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that broccoli-derived nanoparticles (BDN), made of broccoli juice and lipids, prevented dendritic cell (DC) activation by upregulating AMPK anti-inflammatory pathways, thereby reducing chemoattractant molecules like chemokine (C-C) receptors (CCR), chemokine (CXC) ligand (CXCL), and CCLs in the DCs and monocytes [ 116 ]. Similarly, broccoli-derived vesicles rich in GLR, glucobrassicin, and neoglucobrassicin decreased oxidative stress [ 117 ] in Caco-2 cells (colon cells derived from a 72-y-old man with colorectal adenocarcinoma). The SFN treatment transformed the white blood cell monocytes (M1) to anti-inflammatory macrophages (M2) [ 118 , 119 ] through IL10 and signal-transducer and activator of transcription-3 pathways to ameliorate inflammation in bone marrow-derived macrophages [ 118 ], and decreased COX-2 and iNOS activities and increased IL10 and CD36 against chronic inflammation in human cells [ 119 , 126 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of nanoparticulate structures in the samples, their morphology, integrity, and size were analyzed by transmission electron microscopy (TEM), while vesicles Zeta Potential was measured by laser Doppler electrophoresis (LDE) using a Zeta sizer Nano ZS (Malvern Panalytical Ltd., Malvern, UK) and in diffusion barrier mode with water [ 63 ]. The TEM analysis was done by a method previously described [ 63 ].…”
Section: Methodsmentioning
confidence: 99%
“…4, December 2023 190 (Obrenovich et al, 2011). Members of the Brassica oleracea family include cabbage, broccoli, cauliflower, kale, Brussels sprouts, collard greens, Savoy cabbage, kohlrabi, and gai lan, which are antioxidant-rich foods and are natural sources of antioxidants (Al Talebi et al, 2023;Hossain et al, 2022). Broccoli (Brassica oleracea var.…”
mentioning
confidence: 99%